Synthesis, Photophysical and Electrochemical Studies on Triazole-Based Phthalimidodendrimers - Ravivarma, Mahalingam; Satheeshkumar, Chinnadurai; Rajakumar, Perumal (Synlett, 2014)
The synthesis of dendrimers with phthalimide as the surface group and 1,2,3-triazole as bridging unit is described using click chemistry in a convergent approach. The photophysical properties indicate an increase in the molar extinction coefficient as the generation of the dendrimer increases. In cyclic voltammetry studies, the dendrimers show two reversible redox peaks due to formation of a radical anion and a dianion of the phthalimido moiety.
Keywords: dendrimer; 1,2,3-triazole; phthalimide; photophysical and electrochemical